2020
DOI: 10.1021/acsomega.0c02046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Four Common Hydrogels on Amyloid-β (Aβ) Aggregation and Cytotoxicity: Implications for 3D Models of Alzheimer’s Disease

Abstract: The physiochemical properties of hydrogels utilized in 3D culture can be used to modulate cell phenotype and morphology with a striking resemblance to cellular processes that occur in vivo . Indeed, research areas including regenerative medicine, tissue engineering, in vitro cancer models, and stem cell differentiation have readily utilized 3D biomaterials to investigate cell biological questions. However, cells are only one component of this biomimetic milieu. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…(b) Non-cancerous disease models and regenerative medicine Preclinical models for a large spectrum of pathological conditions also take advantage of the elaboration of cellularized materials. Indicatively, corneal stromal disease models can be obtained using collagen bioinks [266], hydrogels can serve as Alzheimer's disease models [267], and liver toxicity can be assessed through core-shell hydrogel fibres [268]. In addition, the field of regenerative medicine exploits macroporous scaffolds to repair or replace defective tissues unable to self-regenerate.…”
Section: Future Trends I: Cellularized Materials In Tissue Engineering (A) Healthy Tissue Modelsmentioning
confidence: 99%
“…(b) Non-cancerous disease models and regenerative medicine Preclinical models for a large spectrum of pathological conditions also take advantage of the elaboration of cellularized materials. Indicatively, corneal stromal disease models can be obtained using collagen bioinks [266], hydrogels can serve as Alzheimer's disease models [267], and liver toxicity can be assessed through core-shell hydrogel fibres [268]. In addition, the field of regenerative medicine exploits macroporous scaffolds to repair or replace defective tissues unable to self-regenerate.…”
Section: Future Trends I: Cellularized Materials In Tissue Engineering (A) Healthy Tissue Modelsmentioning
confidence: 99%
“…In vitro modeling of the more prevalent, sporadic version of such diseases are often more challenging as the replication of disease phenotypes are highly dependent on the physical, chemical and mechanical cues in the microenvironment. A recent study had demonstrated that the amyloid-β plaques formed in an Alzheimer’s disease model may exhibit varying cytotoxicity depending on whether they were confined in 2D or 3D space ( Simpson et al, 2020 ). Agarose, collagen, hyaluronic acid and polyethylene glycol hydrogel cultures were shown to enhance the amyloid-β aggregation towards the larger species which confer lower cytotoxicity as compared to when amyloid-β plaques were found in monolayer cultures.…”
Section: Moving Towards Clinical Translationmentioning
confidence: 99%
“…In any scaffold-based model, thought must be given to the way in which the properties of the chosen scaffold affect Aβ aggregation and Aβ-mediated cytotoxicity. Simpson et al [ 105 ] recently investigated the effect of hydrogel mesh size on Aβ-mediated cytotoxicity and Aβ aggregate size and structure. They found that 3D scaffolds alleviate some Aβ-related cytotoxicity compared to 2D cultures, a phenomenon that is not related to mesh size or bioactivity, but instead likely results from the rapid stabilization of larger, less toxic Aβ aggregates that is common to 3D hydrogels.…”
Section: Modeling Alzheimer’s Diseasementioning
confidence: 99%